(untitled) (Boston, Mass., 2000)
In Secrets of Software Success, the authors investigate the software industry's best practices in order to develop a complete picture of what it takes to build a thriving software business. Drawing on an exclusive worldwide survey of more than 100 global software companies and 450 top executives, Secrets of Software Success presents the first panoramic view of the conditions that influence results for both the product and the service sides of the software industry.
Keywords: Công nghiệp phần mềm máy tính,Computer software industry; Quản trị,Nghiên cứu trường hợp,Management,Case studies